STUDIES ON THE ELECTROPHORETIC PATTERN OF FISH MUSCLE MYOGENS - DEVADASAN, K; NAIR, M RAJENDRANATHAN (Fishery Technology, 2025)
Electrophoretic patterns of the muscle rnyogens of prawnsand some common Indian food fishes of marine and fresh waterorigin were obtained on polyacrylamide gel. It was observed thatthe characteristic band pattern which was species specific and wasnot altered by storage of fish in ice, could be employed as ameans of identification of fish species